Desarrollo de una metodología para el diseño de motores eléctricos de inducción para vehículos (2017)
This document proposes a methodology for the design of electric induction motors for vehicles and proposes the use of equipment designed to meet the needs, since in some cases they select oversized equipment given their commercial availability. However, this type of oversizing requires larger vehicle spaces and adds weight, factors that affect the autonomy of the vehicle. For the development of this project it was necessary to perform the characterization of an induction motor, which was coupled colinearly with a servomotor of Lucas Nèulle company to obtain the curves of the equipment and then measured all its components to realize a Computer simulation in Ansys Maxwell. When making the comparisons between the curves of simulations and experimental it was reached that the similarities are significant and that to realize the design these equipments with computational tools is possible. A sensitivity analysis of all parameters was performed to find which ones affect...